2012
DOI: 10.4236/ape.2012.21006
|View full text |Cite
|
Sign up to set email alerts
|

Gender as a Factor in the Prediction of Performance in Botswana General Certificate of Secondary Education Physical Education Examinations by Coursework and Forecast Grades among Senior Secondary School Students

Abstract: Selection bias is an educational and a social malady which is of concern to every educator especially educational administrator when allocating educational opportunities to learners based on previous performance. Bias in predicting who passes or who fails and hence in selection exists if the same prediction equation is used for different groups, for example, for both gender when in fact such prediction, given the tests involved, is different for male and female learners. As a check for this, there is always th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Similar studies [4] and [6] agreed with the study that there is a significant difference between males and females and that females perform better than males. Ramatlala and Nenty [4] observed that gender influence prediction of students' performance significantly based on cumulative data. The significantly different prediction validities are .473 for males and .551 for females.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar studies [4] and [6] agreed with the study that there is a significant difference between males and females and that females perform better than males. Ramatlala and Nenty [4] observed that gender influence prediction of students' performance significantly based on cumulative data. The significantly different prediction validities are .473 for males and .551 for females.…”
Section: Discussionsupporting
confidence: 89%
“…Ramatlala and Nenty [4] conducted a study in 2011 to investigate gender as a factor in the prediction of performance in Botswana General Certificate of Secondary Education physical education by coursework and forecast grades among secondary schools in Botswana. The sample composed of 2292 (1432 males and 860 females) students who, based on Botswana Examination Council records obtained grades in coursework, forecast and Botswana General Certificate of Secondary Education physical education grades from 2005 through 2008.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The task to develop effective predictors of academic success is a critical issue for educators. Conducting examinations within and at the end of each and every school year is a part of the school curriculum in Botswana and other countries; learners take public examinations to determine their academic standing at each level of education (Ramatlala, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ministry of Education (MOE) in collaboration with Botswana Examination Council (BEC) and Department of Curriculum and Evaluation has recommended school-based continuous assessment (CA) for practical subjects, such as agriculture. Schools assess practical activities carried out by students and grade them for assessment of learning purposes (Ramatlala, 2009). At the end of three years at junior secondary schools, all marks earned by students from practical continuous assessment are combined with theory-based assessment to determine the final grade.…”
Section: Introductionmentioning
confidence: 99%